2021
DOI: 10.25157/ma.v7i2.5513
|View full text |Cite
|
Sign up to set email alerts
|

Strategi Pengembangan Ekonomi Lokal Melalui Kawasan Desa Wisata Berbasis Komoditas Unggulan Kopi Liberika (Kba) Di Desa Kumpai Batu Atas Kecamatan Arut Selatan Kabupaten Kotawaringin Barat

Abstract: The development of the local economy through the concept of a tourism village based on agricultural commodities is a manifestation of a sustainable economy, which is not only creating business opportunities based on the development of agricultural products but also related to community empowerment and sustainability so that they are ready to be competitive in the global market. This study aims to determine the advantages of Kumpai Batu Atas village, South Arut sub-district, West Kotawaringan Regency in develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Masyarakat di Pasar Segiri sekitar Kota Samarinda memang dikenal sebagai masyarakat yang gemar mengonsumsi gula pasir bahkan bumbu masakanpun menggunakan gula pasir untuk menambah kelezatan suatu masakan, sehingga masyarakat bersedia membeli gula pasir sesuai dengan kebutuhan meskipun harga gula mengalami kenaikan karena efek kenaikan Bahan bakar minyak (BBM). Hasil penelitian ini tidak sejalan dengan hasil penelitian yang dilakukan di Kecamatan Arut Selatan Kabupaten Kotawaringin Barat (Rizkiyah & Ramadan Saputri, 2021). 4.…”
Section: Hasil Dan Pembahasanunclassified
“…Masyarakat di Pasar Segiri sekitar Kota Samarinda memang dikenal sebagai masyarakat yang gemar mengonsumsi gula pasir bahkan bumbu masakanpun menggunakan gula pasir untuk menambah kelezatan suatu masakan, sehingga masyarakat bersedia membeli gula pasir sesuai dengan kebutuhan meskipun harga gula mengalami kenaikan karena efek kenaikan Bahan bakar minyak (BBM). Hasil penelitian ini tidak sejalan dengan hasil penelitian yang dilakukan di Kecamatan Arut Selatan Kabupaten Kotawaringin Barat (Rizkiyah & Ramadan Saputri, 2021). 4.…”
Section: Hasil Dan Pembahasanunclassified
“…A study conducted in Kumpai Batu Atas Village, South Arut Sub-district, West Kotawaringin Regency, Indonesia, examined the benefits of KBA's liberica coffee development. The study found that local economic development through the concept of a tourist village based on agricultural commodities is a manifestation of a sustainable economy, which not only creates business opportunities based on agricultural product development but is also related to community empowerment and sustainability so that it is ready to compete in the global market [7]. Overall, improving the local economy requires a comprehensive approach that considers various factors, such as infrastructure, tourism, agriculture and sustainability.…”
Section: Introductionmentioning
confidence: 99%